Regional integration through cross-border cooperation: the case of Ukraine and Türkiye - Fehmi Agca Pamer (II. Rákóczi Ferenc Kárpátaljai Magyar Egyetem, 2025)
Abstract. The regional cooperation is a gradual long-term process and requires steady determination and political commitment. In this regard, protection of the freedom of speech and human rights, corporate governance reform, judicial reform, effective fight against corruption, institutional capacity-building in public administration and strengthening civil society are crucial tasks for any candidate country. Turkish experience with the EU can be valuable for Ukraine in the integration process. Besides, the countries around the Black Sea are providing new opportunities to contribute this process. Crimean Tatars issue deeply effects the Ukraine-Türkiye relations. Ukraine helped to the Crimean Tatar families during their return to Criema after long years of leave and desparation. Turkish people and Crimean Tatar diaspora have developed a positive feeling towards Ukraine. So far Türkiye has clearly supported the territorial integrity of Ukraine, and declared that the Crimea is part of Ukraine. Türkiye provided effective weapon systmes to contribute to the defense of Ukraine territory. Today, the cooperation and partnership continue particularly for joint production of unmanned air vehicles. The solidarity among the Turkish and Ukranian people and the cooperation between the businesses will provide better conditions to improve cross border cooperation to accomplish the regional integration in parallel with the European integration process.
Teljes kiadvány: https://kme.org.ua/uk/publications/rol-bezpeki-v-transkordonnomu-ta-mizhnarodnomu-spivrobitnictvi/
Keywords: Regional integration; Cooperation; Security; Black Sea; Crimean Tatars